Elderly People Undergoing Chemotherapy Treatment: Relationship between Stress, Depressive Symptoms and Hope - Silva, Natália Michelato (2020)
The prevalence of cancer among the elderly has increased in recent decades. Cancer treatment process can lead to increased levels of stress and depression. In this scenario, hope is defined as one of the relevant coping resources. This study aimed to analyze the relationship between stress, depressive symptoms and hope in the elderly undergoing chemotherapy. It is a quantitative, descriptive and cross-sectional study with a non-probabilistic sample of 123 elderly people linked to a general tertiary public hospital in the interior of the State of São Paulo. The results show that the elderly had high levels of perceived stress and hope; 71.5% of the participants did not present depressive symptoms. Levels of stress and hope are negatively correlated, as well as depressive symptoms and levels of hope, suggesting that hope has beneficial effects on stress and depression.